1980
DOI: 10.1182/blood.v55.3.430.430
|View full text |Cite
|
Sign up to set email alerts
|

The inhibition of high and low molecular weight urokinase in plasma

Abstract: The rates of inhibition of high molecular weight (HMW) and low molecular weight (LMW) urokinase (UK) incubated in plasma or with purified antithrombin III (AT-III) were compared. Using a fibrinolytic assay system to determine residual biologic activity, polyacrylamide gel electrophoresis to demonstrate the formation of complexes, and selective immunoprecipitation techniques to identify the plasma inhibitors participating in the neutralization process, it was established that: (A) HMW-UK is inhibited more rapid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
23
0

Year Published

1984
1984
1991
1991

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 21 publications
4
23
0
Order By: Relevance
“…The FCS inhibition was stronger with the 52-kDa form of active u-PA than with the 33-kDa form (c.f. Murano et al, 1980) but clearly the amino-terminal region of u-PA (the portion lacking in 33-kDa u-PA) was not required for inhibition by serum. Pro-u-PA was considerably less affected ( Figure 2), showing that the active site of u-PA was involved.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…The FCS inhibition was stronger with the 52-kDa form of active u-PA than with the 33-kDa form (c.f. Murano et al, 1980) but clearly the amino-terminal region of u-PA (the portion lacking in 33-kDa u-PA) was not required for inhibition by serum. Pro-u-PA was considerably less affected ( Figure 2), showing that the active site of u-PA was involved.…”
Section: Resultsmentioning
confidence: 87%
“…Our results obtained with the RC2A myelomonocytic leukemia cell line show first the partition of active u-PA between bovine serum a2M and cell-surface receptors. Slow inactivation of active u-PA in the medium by serum a2M (Murano et al, 1980;Waller et al, 1983;Straight et al, 1985;Sottrup-Jensen et al, 1989) leads to loss of measurable u-PA activity in the medium, but it is not able to significantly reduce the amount of active u-PA that rapidly binds to the cell surface. This outcome is evidently deter-…”
Section: Discussionmentioning
confidence: 99%
“…The purity of the enzymes was verified by sodium dodecyl sulfate polyacrylamide gel electro phoresis (SDS-PAGE) and inhibitor studies. 3,5,6 Digestion of the BM components was performed at 25°C using matched enzymatic activities. Urokinase failed to degrade laminin significantly, or any of the other components.…”
mentioning
confidence: 99%
“…8 The enzymatic activity of the urokinase preparations were assayed by multiple methods, including plasminogen-dependent fibrinolysis of iodinated fibrin and fluorometric determinations on a fluorogenic substrate: CBZ-Gly-Gly-Argamino methyl coumarin. 5,7,9 Purity of the enzymes employed was confirmed by sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS-PAGE) analysis. [5][6][7] HMW urokinase mediated angiogenesis in eight of ten experiments, whereas LMW urokinase mediated neovascularization in six of ten experiments.…”
mentioning
confidence: 99%
“…5,7,9 Purity of the enzymes employed was confirmed by sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS-PAGE) analysis. [5][6][7] HMW urokinase mediated angiogenesis in eight of ten experiments, whereas LMW urokinase mediated neovascularization in six of ten experiments. In control experiments it was observed that 3 H diisopropylfluorophosphate ( 3 H-DFP) labeled preparations of pure HMW and LMW urokinase failed to mediate neovascularization.…”
mentioning
confidence: 99%